A Triagem neonatal auditiva: conhecimento do Pediatra de Minas Gerais - Ludmila Teixeira Fazito Rezende (2009)
The main part of the newborn hearing screening programs is the early diagnosis of hearing problems and the appropriate educational intervention. So that the screening programs can be successful, it is unquestionable the participation of pediatricians, because they have an important role in the parents decisions related to their newborn child. This study aimed to the investigation of the pediatricians knowledge about the correct procedures, the used techniques and the early diagnosis of the hearing problems in newborns, besides identifying the possible factors related to their knowledge about the newborn hearing screening and its interfaces in Childs Health. It is a cross-section study, performed by inquiry of 93 pediatricians associated to the Minas Gerais Pediatrics Association and through questionnaires answered by 34 pediatricians who participated in a congress of pediatric otolaryngology in Minas Gerais. The variables that provided information about the pediatricians profiles were: years of graduation, which college the doctor graduated from, type of specialization, place and year of the conclusion of the residency, type of pos-graduation and year of its conclusion, environment of work and where their knowledge of hearing and its problems were taken. The variables that investigated the doctors knowledge about the hearing screening programs and its interfaces were: the knowledge about which is the best age to perform the screening, the hearing diagnose and the use of the hearing equipments, the knowledge of the risk factors to deafness and the identifications of which children must pass through the program, the methods of evaluation available and the best moment to perform the screening, which conduct is more appropriated in cases of altered screening and normal triage, educational interventions available, justification to perform the early diagnosis and the role of the pediatrician in those cases. It was analyzed as well if the pediatrician had the knowledge of the difference between the deaf children diagnosed and treated precociously and children with normal hearing, the age to initiate the speech pathologist therapy and their interest to obtain more information about the subject and which are the best ways to get that information. According to the results obtained, only 47 (37%) of de pediatricians were considered knower of the subject. 98% demonstrate that they have knowledge about the possibility of evaluating hearing before 30 days of life, but do not know to identify which exams are available to this evaluation, and only 59% of them send all of the newborns to the hearing screening. Most of the pediatrician do not know until which age the diagnosis must be concluded and just a few (8%) know that a baby with less than 30 days can use hearing aids. There were no statistics differences between pediatricians who know the subject and those who don´t related to the average of time of graduation (p=0,52), nature of the institution of graduation (0,06), period of conclusion of the residency (p=0,17), kind of pediatrics specialization (p=0,76), nature of their work environment (p=0,10), knowledge of which age is possible to evaluate the babies hearing (p=0,18) and knowledge that all of the children must pass through the hearing screening process (p=0,07). The other variables researched demonstrate differences statistically significant between knowers and unknowers. The results of this study suggest a real necessity to establish a more effective way to divulgate to the pediatricians the advantages of the newborn hearing screening, the techniques available to its realization and, mainly, which conducts are more appropriate to the after screening steps. There were no specific characteristics found in the pediatricians profiles that could improve the fact of being a knower or unknower of the subject. Information about the importance of the screening to the development of the childs oral language and the necessity that all of the children must pass through the screening; tend to be common knowledge of the pediatricians. The other variables analyzed suggest to change the knowledge of the pediatricians, emphasizing the importance of specific orientations about the theme, due to the fact that most of them (63%) were classified as unknowers of the procedures and conducts involving the screening.